Clinicopathological Characteristics and Prognosis of Upper Gastric Cancer Patients in China: A 32-Year Single-Center Retrospective Clinical Study - Yingbo Gong; Pengliang Wang; Zhi Zhu; Junyan Zhang; Jinyu Huang; Huimian Xu (Gastroenterology Research and Practice)
Purpose. Upper or proximal gastric cancer occurs in the upper third of the stomach between the cardia and a line connecting the greater and lesser curvatures. As it differs from other gastric cancers in pathology and prognosis, we evaluated patient and disease characteristics that might guide improved treatment and survival of upper gastric cancer. Methods. We conducted a retrospective analysis of 649 patients with upper gastric cancer and 1551 patients with lower gastric cancer and R0 radical surgery at our institution between January 1980 and December 2012. Results. Survival after radical surgery for upper gastric cancer was 77.8% at 1 year, 49.6% at 3 years, and 41.1% at 5 years. The corresponding rates for lower gastric cancer were 85.9%, 60.0%, and 57.2% (p<0.001). Upper gastric cancer had a poor prognosis. Sex (p=0.036), tumor diameter (p=0.001), macroscopic type (p<0.001), pTM stage (p<0.001), tissue differentiation type (p=0.003), and serosal invasion (p=0.034) were independently associated with lymph node metastasis. The macroscopic type (p=0.045), lymphovascular tumor emboli (p=0.021), and pTNM stage were independently associated with recurrence and metastasis. Survival of 333 patients with D2 total gastrectomy was 81.3% at 1 year, 54.4% at 3 years, and 45.2% at 5 years. The corresponding rates for 316 proximal gastrectomy patients were 75.4%, 44.9%, and 36.7%. Radical total gastrectomy had better survival than radical proximal resection. Conclusions. Upper gastric cancers were more aggressive, had a worse prognosis, and were more prone to recurrence and metastasis compared with lower gastric cancers. Survival was better after total gastrectomy than after proximal resection.